FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CSR, SEBUAH STUDY EMPIRIS PERUSAHAAN MANUFAKTUR - Kurnia Putri; Fitra Dharma; Dewi Sukmasari (Jurnal Akuntansi dan Keuangan (JAK), 2020)
This studi aims to determine the effect of Board of Commissioners, Profitability, Media Exposure, and Foreign Ownership on CSR disclosure. Population used in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2016-2018, and the samples obtained has 411 observation selected using purposive sampling method in order to obtain samples accordance with the research objectives. Analysis technique used is multiple regression. The result shows that Board of Commissioners, Media Exposure, and Foreign Ownership has a significant positive effect on the Disclosure of Corporate Social Responsibility. While Profitability dosen not affect the Disclosure of Corporate Social Responsibility.